Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan melalui Disiplin Kerja pada PT. Padma Soode Indonesia - Salma Putri; Supardi Supardi; Agus Dharmanto (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze leadership style on employee performance through work discipline at PT. Padma Soode Indonesia. With three variables, namely leadership style as the independent variable (X), employee performance as the mediating variable (Z), and finally work discipline as the commitment variable (Y). This form of research examines quantitatively with primary and secondary data used in this investigation. Direct observation, interviews, and questionnaires were used to collect primary data. The author uses library data from documentation, reference books and research journals as secondary data. Processing of data that is ready to be obtained must be carried out using the SPSS version 26 program. This research stage includes a planning stage, an implementation stage, and a writing stage. The population of this study was 300 employees (respondents) in the stamping division, who used simple random sampling techniques to take samples from the existing population by means of simple random sampling, which can be done using a lottery model, namely all members of the population are given serial numbers, Then random numbers were taken with the number of numbers taken, according to the expected sample size and using the Slovin formula, the population was 171 employees (respondents). The results of this research show that leadership style influences employee performance in a statistically tested manner. Leadership style's influence on work discipline has not been statistically tested. Work discipline has a statistically proven effect on employee performance. Leadership style influences employee performance through statistically proven work discipline. Apart from that, the results of this research for the leadership style variable, advice that can be given is that leaders must communicate frequently with their subordinates in order to build trust and relationships, increase involvement and productivity, and generate feedback and ideas. For the work discipline variable, the advice that can be given is that employees must communicate with all team members in order to increase collaboration and cooperation, increase collaboration and cooperation, increase coordination and efficiency, build strong relationships. For employee performance variables, suggestions that can be given are that employees must meet the given deadlines in order to increase efficiency and productivity, build trust and credibility, improve the quality of work, support the achievement of goals.